Effect of Temperature on Gas and Liquid Products Distribution in Thermal Cracking of Nigerian Bitumen - OLAREMU, ABIMBOLA GEORGE; ODEBUNMI, Ezekiel Oluyemi; ANDERSON, Jim A (Iraqi Journal of Chemical and Petroleum Engineering, 2021)
The increasing population growth resulting in the tremendous increase in consumption of fuels, energy, and petrochemical products and coupled with the depletion in conventional crude oil reserves and production make it imperative for Nigeria to explore her bitumen reserves so as to meet her energy and petrochemicals needs. Samples of Agbabu bitumen were subjected to thermal cracking in a tubular steel reactor operated at 10 bar pressure to investigate the effect of temperature on the cracking reaction. The gas produced was analyzed in a Gas Chromatograph while the liquid products were subjected to Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Heptane was the dominant gas produced in bitumen cracking at all temperatures and the reaction products show a distribution of lighter hydrocarbons most of which are in the gasoline range. The product distribution of bitumen conversion depends strongly on the cracking temperature and the oil produced contains the valuable liquid fractions. The products of thermal cracking of bitumen can be classified into the following groups; alkanes, alkenes, amines, aromatics, alkanoic acids, alkanols, esters, ethers, ketones, sulphur compounds, and nitrogen compounds. The activation energies of the products formed were determined. The LNG produced all have unusually low values activation energy (hence easily converted) pointing to the high quality of Agbabu crude     The conversion process was affected by the reaction time and suggests that the transformation of bitumen into smaller fractions follows a definite reaction scheme in which the heavy oil transformed to lower fractions and was subsequently converted to smaller liquid fractions and gases.